A Neonatal Patient Diagnosed with Chromosome 18p 11.1 Microdeletion Syndrome Presented with Trisomy 18Like Phenotype - Deepa Banker; Bhavdeep Mungala; Zankhana Parekh; Shachi Ganatra; Vimal Maheshwari; Yashica Raj; Utsav Patel; Digant Patel; Kishan Chamar; Vasu Solanki (Hindawi Limited, 2023)
Microdeletion of the short arm of chromosome 18 is one of the most common chromosome deletion syndromes. Its estimated frequency is 1 in 50,000 live-born infants, with female prevalence over males. Around 150 cases have been described till now. The reported abnormalities include growth deficiency, hypotonia, microcephaly, dysmorphic facial features such as ptosis, epicanthal folds, hypertelorism and micrognathia, and relatively small hands and feet. Our patient was a full-term low birth weight (2150 gm) female newborn, showing cleft upper lip and palate (hard and soft palate), bilateral congenital Talipes Equinovarus with rocker bottom foot, microcephaly, atrial septal defect. She was initially conservatively managed with gavage feeding, then shifted into paladai feeding of expressed breast milk. A multidisciplinary approach was adopted due to various malformations and for the potential occurring complications. To our knowledge, this is the first case diagnosed during the neonatal period.